STRENGTH RESEARCH OF ELEMENTS OF THE BUNKER WAGON CONSTRUCTION (Transport systems and technologies, 2018)
The article deals with the theoretical and experimental study of the strength of the structural elements of the hopper car covered for grain and other food cargoes. The results of experimental and theoretical studies of the stress-strain state of the hopper car frame by the finite element method (fem) are analyzed. Analysis of the results showed that the convergence of the results of theoretical and experimental studies is 84% – 87%, which is a satisfactory result and confirms the adequacy of the design scheme and the reliability of the possible results of calculations for other elements of the design of the hopper car.Experimental studies were performed by the tensometric method. Special attention was paid to the measurement of deformations in the pivot assembly as the most loaded element.Data processing of static strength tests was performed using automated complexes of experimental data processing using statistical methods. Despite the modernization and strengthening sordevolo node for hopper model 19-4152, the maximum voltage at that node 98,5% of the permissible normative values. This indicates that the pivot point remains one of the most stressed elements of the car and requires detailed study when performing further studies.The analysis of published literature sources shows that the problems associated with the strength of the hopper cars are relevant not only in Ukraine but also in the cis countries.
Keywords: hopper car, element strength, design and experimental stresses